A cross-sectional analysis of yoga experience on variables associated with psychological well-being - Parkinson, Tracie D.; Smith, Stephen D. (Frontiers in Psychology, 2023)
Previous research has identified numerous physical, psychological, and spiritual benefits associated with the practice of yoga. Indeed, yoga has been linked with improved quality of life, reduced stress, and numerous markers of psychological well-being. In the current research, a cross-sectional design was used to examine whether the psychological benefits associated with yoga only apply to long-term practitioners or whether more “casual”, intermittent yoga experience could produce positive outcomes. An American population of long-term practitioners (n = 129), intermittent practitioners (n = 161), and non-practitioners (n = 164) completed online self-report measures of emotional regulation, trait mindfulness, self-compassion, interoceptive awareness, and spiritual intelligence variables. The results indicated that long-term (LT) practitioners scored higher than intermittent experience (IE) practitioners on measures of mindfulness (MLT = 137.3; MIE = 127.6), interoceptive awareness (MLT = 3.4; MIE = 3.1), self-compassion (MLT = 3.4; MIE = 3.1), and spiritual intelligence (MLT = 63.5; MIE = 55.5; all p-values < .05). Intermittent practitioners scored higher than no-experience (NE) group on interoceptive awareness (MIE = 3.1; MNE = 2.7) and spiritual intelligence (MIE = 55.5; MNE = 46.6; both p-values < .05). Contrary to our hypotheses, yoga experience had no effect on depression, anxiety, or stress levels. Separate mediation analyses demonstrated that interoceptive awareness, spiritual intelligence, mindfulness, and self-compassion each mediated the relationship between yoga experience and emotion dysregulation. Furthermore, emotion dysregulation mediated the relationship between yoga experience and depression, anxiety, and stress. Taken together, the results of this study suggest that long-term practitioners experience more benefits compared to intermittent and non-practitioners, and that the mechanisms underlying these benefits are multi-faceted.